2023
DOI: 10.3390/medicina59020307
|View full text |Cite
|
Sign up to set email alerts
|

Severe Hemoperitoneum due to Ovarian Bleeding after Transvaginal Oocyte Retrieval with Surgical Management: A Retrospective Analysis and Comprehensive Review of the Literature

Abstract: Background and Objectives: Severe hemoperitoneum of ovarian bleeding origin is a rare but potentially life-threatening complication of transvaginal oocyte retrieval (TVOR) procedure. The study aimed to present a case series of surgically managed patients from our clinic with hemoperitoneum caused by ovarian bleeding after TVOR, as well as to perform a comprehensive literature review in order to summarize and analyze all published cases with this condition and their management. Materials and Methods: The data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In a more detailed literature search for cases of haemoperitoneum caused by ovarian haemorrhage post-TVOR, a retrospective study reported only 3 cases of haemoperitoneum due to ovarian haemorrhage post-TVOR out of 3656 cases recorded (0.08%) 11. A comprehensive literature review had similar findings, stating that the incidence of haemoperitoneum due to ovarian bleeding was 0.09% of patients in the pooled analysis of 31 555 patients who received TVOR 4…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In a more detailed literature search for cases of haemoperitoneum caused by ovarian haemorrhage post-TVOR, a retrospective study reported only 3 cases of haemoperitoneum due to ovarian haemorrhage post-TVOR out of 3656 cases recorded (0.08%) 11. A comprehensive literature review had similar findings, stating that the incidence of haemoperitoneum due to ovarian bleeding was 0.09% of patients in the pooled analysis of 31 555 patients who received TVOR 4…”
Section: Discussionmentioning
confidence: 85%
“…In a comprehensive literature review, 43 cases of haemoperitoneum caused by ovarian haemorrhage due to TVOR were recorded out of 18 studies reviewed. Out of these 43 cases, only 1 case was treated with unilateral ovariectomy with suturing and electrocoagulation being the most common treatment options 4. In the case of ovarian haemorrhage and acute life-threatening bleeding, and when the contralateral ovary appears normal, oophorectomy can be justified given the greater risk and little benefit to leaving the ovary in place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of thrombosis and bleeding was compared to the rate of patients' ongoing IVF-ET with data available in Literature. [24][25][26]…”
Section: Methodsmentioning
confidence: 99%